STUDI PERBANDINGAN KINERJA GEDUNG BETON BERTULANG SRPMK 6 LANTAI DENGAN MENGGUNAKAN METODE PUSHOVER DAN NONLINEAR TIME HISTORY ANALYSIS - Syaiful Anam; Bantot Sutriono; Retno Trimurtiningrum (Fakultas Teknik, Universitas Wiraraja, 2020)
Indonesia is one of the earthquake-prone countries in the world. To reduce the impact of earthquakes, especially the missing life due to building collapse, the behavior or performance of buildings against the earthquakes is one of the most important things to consider. Therefore, inelastic or nonlinear analytical calculations must be performed. Some methods for calculating nonlinear analysis are static nonlinear pushover analysis and inelastic dynamic time history analysis. This study compares the performance results of the pushover analysis and time history analysis using the earthquake records from San Fernando, Morgan Hill and Kobe for a 6-story SRPMK reinforced concrete building. From the results of the pushover analysis and time history analysis, the same level of performance is obtained, which is IO (Immediate Occupancy) category for both X and Y directions. The displacement target obtained from the pushover analysis is 0.092 m for the X direction and 0.096 m for the Y direction. While the maximum displacement obtained from the results of time history analysis is 0.0129 m for the X direction and 0.005 m for the Y direction from the Kobe earthquake and San Fernando earthquake records.